1995
DOI: 10.1143/jjap.34.3240
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Generation of Linearly Polymerized Liquid Crystal Aligning Layers Comprising Novel, Integrated Optically Patterned Retarders and Color Filters

Abstract: For the first time photo cross-linking of linearly polymerizable polymers (LPPs) is shown to induce uniaxial planar alignment in adjacent liquid crystal polymer (LCP)-layers on single substrates. Ways and novel materials allowing integration of LPP-aligning layers with optical retarders in patterned, hybrid LPP-LCP-configurations with freely adjustable optical axes are presented. The novel multifunctional, anisotropic photopolymer configurations are shown to render in-situ optical retarders and polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(104 citation statements)
references
References 7 publications
0
103
0
Order By: Relevance
“…In that case, the gray scales have to be produced by changing the polarization direction of the light. 10 A complex pattern containing gray scales was recorded in the polymer film using a negative of a photograph. Compared to the patterns shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that case, the gray scales have to be produced by changing the polarization direction of the light. 10 A complex pattern containing gray scales was recorded in the polymer film using a negative of a photograph. Compared to the patterns shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(E)-(1R,4R) -2 -͑4 -͑4 -hexyloxybenzoyloxy ͒phenyl -methene͒ menthan-3-on ͑NRM͒ and poly͓4͑6-acryloyloxyhexyloxy͒ benzoyloxy͒benzonitrile͔ ͑polyCN͒ were synthesized according to previously published procedures. 8,10 The melting point of NRM was 96°. The molecular weight (M n ) of polyCN was 6100 g/mol and the polydispersity was 1.…”
Section: A Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal was to achieve optically perfect photo-patterned LCP thin-films with azimuthal and zenithal tunable optical anisotropy on single LPP-photo-aligned substrates. In the mid-1990s Schadt et al demonstrated and patented for the first time the feasibility of surface alignment and pattering of planar liquid crystal pre-polymer films on single substrates [54]. Apart from uniaxial planar LCP-alignment it was shown that the transfer of LPP-bias tilt into LCP-films was possible and also that stacking of different LCP-films with azimuthally different slow optical axes of index ellipsoids was feasible [55].…”
Section: Photo-alignment/pattering Of Liquid Crystal Polymers (Lcps)mentioning
confidence: 99%
“…In this way, a customized LC director distribution can be achieved to offer special designed optical functions. Many photonic devices can be achieved via patterned alignment, including patterned retarders [9,10], Q-plates [4,5], LC gratings [11,12], LC lenses [13][14][15], and polarization converters [16][17][18], etc., which could find many important applications in beam shaping [4], imaging system [13,14], Complementary Metal Oxide Semiconductor (CMOS) sensor system [19] and 3D display [10], etc.…”
Section: Introductionmentioning
confidence: 99%